(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the role of innovative technologies in education and highlights their impact on learning. The article discusses the evolution of educational technologies, from traditional methods to modern tools such as AI, VR, digital learning platforms, and IoT-based smart classrooms. The article highlights how AI personalizes learning, gamification increases engagement, and the metaverse enhances virtual learning. Overall, the article provides a clear and understandable overview of how technology is transforming education for a more interactive and inclusive future.